Isu-Isu Kritis Dalam Pendidikan Islam - Ficky, Ficky Uwais Alqarny; Sukari, Sukari (Faculty of teaching training and education, 2024)
This research aims to investigate critical issues in Islamic education that have significant impacts on the current education system. The study seeks to provide crucial insights for stakeholders in the field of education, including the government, educational institutions, and the general public, to engage in improving the education system to address these critical issues and ensure that all individuals have equal opportunities to receive quality education. The research adopts a Literature Review approach, involving the collection of literature data, reading, analyzing, and recording relevant research materials. This includes utilizing document studies on the results of previous research. Data collection is conducted by searching journals on various electronic media such as digital libraries and the internet. The search for journals is carried out through Google Scholar and academic literature related to critical issues in Islamic education. The results of the research indicate that critical issues in Islamic education can be divided into two categories: internal factors, including Power Relations and the Orientation of Islamic Education, Curriculum Issues, Learning Approaches/Methods, Professionalism and Human Resource Quality, and Education Costs. External factors include Dichotomic, To General Knowledge, Lack of Spirit of Inquiry, Memorization, and Certificate Orientation. The solution to addressing these critical issues is to return Islamic education to its natural state, designing education in such a way that learners can develop their potential naturally and creatively in an atmosphere of freedom, togetherness, and responsibility. Islamic education is oriented towards a Process of Awareness, a Humanization Process, and the Cultivation of Noble Character. Keywords: Critical Education, Educational Issues, Islamic education